Assessing tactile acuity in oral tissues: Challenges of stimulus development. (October 2022) - Miles, Brittany L.; Berkowitz, Kevin; Mueller, Hollie; Simons, Christopher T.
Highlights: Tongue shows greater discriminability than palate or gums for tactile percepts. Hard palate more sensitive than gums to differences in surface roughness. Palate and gums show similar tactile acuity to fingertips for all percepts. Stimuli designed for lingual use are not necessarily apt for all oral tissues. Abstract: The human oral cavity is comprised of a variety of mechanosensitive structures likely involved in food texture perception. However, studies evaluating oral tactile acuity are often limited to the tongue, which may miss relevant contributions coming from other oral tissues. To address this knowledge gap, the relative acuities of three oral soft tissues, the tongue, the hard palate, and the gums, were assessed in adults (n = 90) using the forced-choice staircase technique. It was hypothesized the tongue would show superior acuity over the more keratinized surfaces due to its flexible nature and thinner epidermis, while the palate would be superior to the gums due to the palate's high density of mechanoreceptive endings. Discrimination acuities for the tissues were assessed using three different sets of stimuli previously adapted for use on the tongue, punctate-pressure (F; 0.0044–0.010 g), edge-sharpness (∡; 90.0–135.0°), and surface roughness (Ra; 0.177–0.465 μm), via a just-noticeable-difference (JND) task. Participants were found to have significantly lower JNDs with their tongues for all percepts tested (p ≤ 0.019, all), while discrimination thresholds on the palate were only significantly lower than those seen on the gums in the roughness assessment condition (p = 0.013). Both the gums and palate, however, showed similar acuity to previously obtained sensitivity values for the fingertip for all tested percepts. These findings do suggest that all tissues are highly sensitive and likely critical for texture perception, but the lack of significant difference between the palate and gums may also be partially attributable to the stimuli being ill-suited for use in palate assessments. While all stimuli used were well-suited for use in lingual evaluations, the palate's curved geometry and limited accessibility made application and evaluation of both the punctate-pressure and edge sharpness stimuli challenging. Further adaptation of stimuli to optimize them for use on more-rigid tissues could provide further insight into the relative acuity of these different tissues.